Complex adaptive leadership : embracing paradox and uncertainty (Gower, 2014)
Nick Obolensky argues that leadership should not be something only exercised by nominated leaders. It is a complex dynamic process involving all those engaged in a particular enterprise. The theoretical background to this lies in complexity science and chaos theory - spoken and written about in the context of leadership for the last 20 years, but still little understood. We all seem intuitively to know leadership 'isn't what it used to be' but we still cling to old assumptions which look anachronistic in changing and challenging times. Nick Obolensky has practised, researched and taught leadership in the public, private and voluntary sectors. In this exciting book he brings together his knowledge of theory, his own experience, and the results of 19 years of research involving 2,500 executives in 40 countries around the world. The main conclusion from that research is that the more complex things become, the less traditional directive leadership is needed. Those operating in the real world, nonetheless, need ways of coping. The book is focused on helping practitioners struggling to interpret and react to increasingly VUCA (Volatile, Uncertain, Complex, Ambiguous) times. The book will particularly appeal to practitioners wishing to improve their leadership effectiveness as well as for students and researchers in the field of leadership